(tanθ-1)/(sinθ-cosθ)=secθ
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 16:02:29
(tanθ-1)/(sinθ-cosθ)=secθ(tanθ-1)/(sinθ-cosθ)=secθ(tanθ-1)/(sinθ-cosθ)=secθ(tanθ-1)/(sinθ-cosθ)=cosθ
(tanθ-1)/(sinθ-cosθ)=secθ
(tanθ-1)/(sinθ-cosθ)=secθ
(tanθ-1)/(sinθ-cosθ)=secθ
(tanθ-1)/(sinθ-cosθ)
=cosθ(tanθ-1)/(sinθ-cosθ)cosθ
=(sinθ-cosθ)/(sinθ-cosθ)cosθ
=1/cosθ
=secθ
化简(sinθ-cosθ)/(tanθ-1)A.tanθ B.sinθ C.-sinθ D.cosθ
cos θ/(1-tan θ)怎样化成cos θ/[(cosθ-sinθ)/cosθ]
证明tan^θ-sin^2θ=tan^2θsin^2θ证明(1)tan^θ-sin^2θ=tan^2θsin^2θ(2)sin^4x+cos^4x=1-2sin^2cos^2x(31-tan^2x/1+tan^2x=cos^2x-sin^2x
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
sin^2(θ)+4cosθ/sin(90-θ) -1/tan(90-θ)
求证:sin³θ(1+cotθ)+cos³θ(1+tanθ)=sinθ+cosθ
1/tanθ + sinθ/1+cosθ
1/cosθ*sinθ等于tanθ吗
化简(sinθ-cosθ)/(tanθ-1)
化简tanθ-1分之sinθ-cos等于
求证sinθ(1+tanθ)+cosθ(1+1/tanθ)=1/sinθ+1/cosθ
求证2(cosθ -sinθ )/1+sinθ +cosθ =tan(π/4-θ /2)-tanθ /2
求证:2(cos θ -sin θ )/(1+sinθ +cosθ)=tan(∏/4- θ /2)-tan(θ /2)
已知sinθ+cosθ=((√3)+1)/2,求(sinθ)/(1-(1/tanθ))+(cosθ)/(1-tanθ)的值.
已知sinθcosθ>0 sinθtanθ
化简(√3cosθ+sinθ)/(√3sinθ-cosθ)不要跳步,内容:两角和差的正切原式=[(√3cosθ+sinθ)/cosθ]/[(√3sinθ-cosθ)/cosθ]=(√3+tanθ)/(√3tanθ-1)= -(tanπ/3+tanθ)/(1-tanπ/3tanθ)= -tan(π/3+θ)
若兀/4tanθB.cosθ>tanθ>sinθC.sinθ>tanθ>cosθD.tanθ>sinθ>cosθ